Beware Greeks Bearing Gifts: The Greek agora revisited as a discontinuous subject of historical knowledge. - Basson, Steve (Society of Architectural Historians, Australia and New Zealand, 2004)
From the conventional perspective of Western architectural history, the urban formations of the ancient Greek polis and agora represent privileged organizations of space. An understanding of these Greek conditions and experiences of the urban realm are also seen necessary for the continued preservation of those ideals of democratic inclusion, equity and freedom associated with our own contemporary public terrains of urban existence. But to what extent can Greek conceptions of the agora be said to correspond and merge seamlessly with the spatial norms of today? To accede to the demands of historical tradition by embracing the properties of the linear and trans-historical is to conceive the Greek agora as a timeless and essential product of knowledge that can be employed as the pure model by which to gauge current conditions and perceived failings of the public realm. On the other hand, by beginning to address what was especial to the limits of perception and behaviour of the Greek agora, would contest the old assumptions and canons of historicist continuity, immutability and origin that legitimate a particular view of the past. Through a contextualized reading of some of the rationalities, practices and constraints particular to the arena of the Greek agora, the following discussion focuses upon what may define the otherness of Greek urban and architectural space and with what distances it from the ground upon which our contemporary architectural and urban possibilities of public space are founded.